2020
DOI: 10.1016/j.euroecorev.2020.103569
|View full text |Cite
|
Sign up to set email alerts
|

An economic model of the meat paradox

Abstract: Many individuals have empathetic feelings towards animals but frequently consume meat. We investigate this "meat paradox" using insights from the literature on motivated reasoning in moral dilemmata. We develop a model where individuals form self-serving beliefs about the suffering of animals caused by meat consumption in order to alleviate the guilt associated with their dietary choices. The model predicts that the price of meat has a causal effect on individuals' beliefs: high prices foster realism by loweri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 48 publications
1
27
0
2
Order By: Relevance
“…In terms of elasticities, a 1% higher PMJ score produces a rise of 0.60% in the PMJ (p < 0.001). This positive relationship is in line with previous work looking at the link between diet and pro-meat justifications (Loughnan, Haslam, and Bastian 2010;Hestermann, Le Yaouanq, and Treich 2020).…”
Section: Pro-meat Justificationssupporting
confidence: 90%
See 3 more Smart Citations
“…In terms of elasticities, a 1% higher PMJ score produces a rise of 0.60% in the PMJ (p < 0.001). This positive relationship is in line with previous work looking at the link between diet and pro-meat justifications (Loughnan, Haslam, and Bastian 2010;Hestermann, Le Yaouanq, and Treich 2020).…”
Section: Pro-meat Justificationssupporting
confidence: 90%
“…Several contributions have suggested that individuals have imperfect knowledge about the negative externalities of meat consumption on animals, and that this ignorance is related to motivated reasoning (Loughnan, Haslam, and Bastian 2010;Loughnan, Bastian, and Haslam 2014;Graça, Calheiros, and Oliveira 2016;Piazza and Loughnan 2016;Hestermann, Le Yaouanq, and Treich 2020;Espinosa and Stoop 2020). We do not focus here on emotional or strategic concerns, but rather build on this recent behavioral-economics literature showing that individuals may have incentives to ignore the most impactful messages (see the theoretical-background subsection).…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…A related implication concerns the meat paradox hypothesis: consumers form self‐serving beliefs in order to reduce the feeling of guilt associated with meat eating (Loughnan et al 2010 ; Hestermann et al 2020 ). That is, people like to eat animals but do not like to feel responsible for the suffering and slaughter of animals, and look (perhaps subconsciously) for excuses and justifications.…”
Section: Some Demand Side Issuesmentioning
confidence: 99%